(3BKGQ GdHdGO hCNHGQ GdYHGOs - (3RcQjG Hf eMeO Hf eMehO,GdnbrRphjfj, CHh jMji YeGO GdOjf,J (B682 (3g` s ((3MSjf Hf YKeGf Hf MSjf GdMGaX GdeYde s)
(3ChdgG (B:s
(3CeG HYO jbhd GdYHO RcQjG Hf eMeO Hf eMehO GdbRhjfi s
(3BNQgG (B:s
(3Ef de jdbhG GdSja ai GdHMQ hdG jNQL GdSecI cGf bhJge ef gfG Edi ggfG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3ai ChdgG LOGhd HCSeGA HdGO GdCbGdje s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B183s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B9s
Keywords: (3GdLZQGajG h GdHdOGfs